The method of strengtheningcharacter education values for students in industrial revolution 4.0 era - Luluk Ifadah (ATTARBIYAH: Journal of Islamic Culture and Education, 2019)
This study aims at providing an understanding of the Method of Strengthening the character education value for students in the Industrial revolution 4.0 era. In writing this study seeks to present methods that are relevant for strengthening the value of character education in students in Industrial revolution 4.0 era. The results showed that the method of strengthening the value of character education for students in the Industrial Revolution 4.0 era included: a) Exemplary Method, b) Pilot Method, c) Habituation Method, d) Repetition Method, e) Training Method, f) Motivation Method. The challenges are the readiness of educational institutions and educational resources, the readiness of families, the still weak control and support of elements of society, and the shift in the community's paradigm from productivity to consumptive. Then opportunities that can be exploited are self-development faster, opportunities to become innovators in every field of expertise, students from all walks of life have the same opportunity in strengthening competitiveness in the global era.